INTENSITAS SERANGAN PENGGEREK KAYU DI LAUT PADA BEBERAPA JENIS KAYU - Mohammad Muslich; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1988)
One hundred  fifty  pieces   of  wood  from  five species  were exposed   to marine  borers in three   different locations  for periods   up  to  three  months   at  different   periods.   The  tests  were  conducted   around  Jak9rta  Gulf  i.e  about   3  km  off shore from Mauk  from  January  -   June  1986, Rambut Island from  July - November 1986, and Puntung, Java lsland from  November 1986   -   February 1987. The  result shows  that  most  of  the  wood  tested  were  badly  attacked   by Molluscs  belonging  to the specise Martesia striata  Linne.,   Teredo  bartschi  Clap.,   Dichyathifer  manni  Wright.,  and Bankia campanellata Molli Roch.  Diospyros  celebica Bahh, wood  seems  to  be resistant  to  marine  borers.   The  intensity   of  borer attack  on the woods  in the three locations  are not significantly different.